Polymerization of the Actin-Like Protein MamK, Which Is Associated with Magnetosomes - Taoka, Azuma (American Society for Microbiology (ASM), 2007)
The recombinant actin-like protein MamK was purified from Escherichia coli and used as an antigen to generate the anti-MamK antibody. Immunostaining studies showed a linear distribution of MamK in Magnetospirillum magnetotacticum cells and of MamK in association with magnetosomes. Moreover, we demonstrated that MamK polymerizes into filamentous bundles in vitro.